THE EFFECT OF CASH FLOW AND ACCOUNTING PROFIT ON THE STOCK PRICE OF FOOD AND BEVERAGE COMPANIES IN THE INDONESIA STOCK EXCHANGE - Pelitawati, Dyah; Kurniawati, Ony; Wulandari, Fitria (Sekolah tinggi ilmu ekonomi pemuda, 2023)
This study aims to test and analyze cash flow and accounting profit on stock prices in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX). The sampling technique was carried out using the purposive sampling method, and we obtained 14 companies that became research samples. The observation period is 5 years, namely 2016 - 2020 so the analysis data obtained is 70. The data was tested using Multiple Linear Regression Analysis, t test, F test, and Coefficient of Determination. The results of this study using the t test show that the operating cash flow, investment cash flow, and funding cash flow variables partially have no significant effect on the stock price variable, and the accounting profit variable partially has a positive and significant effect on the stock price variable. While the results of research using the F test show that simultaneously the operating cash flow variable, investment cash flow, and funding cash flow have a significant effect on the stock price variable. The results of the study using the coefficient of determination (R2) variable operating cash flow, investment cash flow, funding cash flow, and accounting profit together affect the variable stock price of 42.9%. While the remaining 57.1% is influenced by other variables outside of this regression equation.